2019
DOI: 10.1111/eth.12849
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution and behavioral plasticity following introduction to an environment with reduced predation risk

Abstract: Adaptive behavioral plasticity can play a beneficial role when a population becomes established in a novel environment if environmental cues allow the expression of appropriate behavior. Further, plasticity itself can evolve over time in a new environment causing changes in the way or degree to which animals respond to environmental cues. Colonization events provide an opportunity to investigate such relationships between behavioral plasticity and adaptation to new environments. Here, we investigated the evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…in Trinidadian guppies when prey shift to a situation with relaxed predation pressure (Westrick et al, 2019). Our results during the second transition match with the only other study reporting a correlation between ancestral plasticity and evolution at the molecular level.…”
Section: Interplay Of Plasticity and Evolution In Driving Rapid Metabolomic Shifts Through Timesupporting
confidence: 87%
See 1 more Smart Citation
“…in Trinidadian guppies when prey shift to a situation with relaxed predation pressure (Westrick et al, 2019). Our results during the second transition match with the only other study reporting a correlation between ancestral plasticity and evolution at the molecular level.…”
Section: Interplay Of Plasticity and Evolution In Driving Rapid Metabolomic Shifts Through Timesupporting
confidence: 87%
“…This matches the reduced plasticity for multiple life‐history, morphology and behaviour traits in D . magna during the second transition (Stoks et al, 2016), as also has been observed in Trinidadian guppies when prey shift to a situation with relaxed predation pressure (Westrick et al, 2019). Our results during the second transition match with the only other study reporting a correlation between ancestral plasticity and evolution at the molecular level.…”
Section: Discussionmentioning
confidence: 57%
“…Czesak et al, 2006; Via & Lande, 1985), as has been observed in guppies for other traits (e.g. Handelsman et al., 2013; Torres‐Dowdall et al, 2012; Westrick et al, 2019).…”
Section: Introductionmentioning
confidence: 72%
“…We found longer genitalia in the source population that coexists with major predators, consistent with the sexual conflict hypothesis (Arnqvist & Rowe, 2002) since forced copulation rates are higher in high‐predation environments (Evans et al., 2011; Liley & Luyten, 1985; Magurran & Seghers, 1994). In these same populations, females did not exhibit a preference for more colourful males (Westrick et al, 2019), further suggesting mate choice may not be as important as sexual conflict in this case, but introduced females also spent less time investigating and associating with males (Westrick et al, 2019), which suggests gonopodia should have increased, not decreased in length, to improve forced copulations as a strategy to mate with unresponsive females. Thus, our results are consistent with the growing body of work implicating sexual conflict in gonopodium evolution (e.g.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation